Proteoform-Resolved FcɤRIIIa Binding Assay for Fab Glycosylated Monoclonal Antibodies Achieved by Affinity Chromatography Mass Spectrometry of Fc Moieties - Lippold, Steffen; Nicolardi, Simone; Wuhrer, Manfred; Falck, David (Frontiers in Chemistry, 2019)
Fcɣ receptors (FcɣR) mediate key functions in immunological responses. For instance, FcɣRIIIa is involved in antibody-dependent cell-mediated cytotoxicity (ADCC). FcɣRIIIa interacts with the fragment crystallizable (Fc) of immunoglobulin G (IgG). This interaction is known to be highly dependent on IgG Fc glycosylation. Thus, the impact of glycosylation features on this interaction has been investigated in several studies by numerous analytical and biochemical techniques. FcɣRIIIa affinity chromatography (AC) hyphenated to mass spectrometry (MS) is a powerful tool to address co-occurring Fc glycosylation heterogeneity of monoclonal antibodies (mAbs). However, MS analysis of mAbs at the intact level may provide limited proteoform resolution, for example, when additional heterogeneity is present, such as antigen-binding fragment (Fab) glycosylation. Therefore, we investigated middle-up approaches to remove the Fab and performed AC-MS on the IgG Fc to evaluate its utility for FcɣRIIIa affinity assessment compared to intact IgG analysis. We found the protease Kgp to be particularly suitable for a middle-up FcɣRIIIa AC-MS workflow as demonstrated for the Fab glycosylated cetuximab. The complexity of the mass spectra of Kgp digested cetuximab was significantly reduced compared to the intact level while affinity was fully retained. This enabled a reliable assignment and relative quantitation of Fc glycoforms in FcɣRIIIa AC-MS. In conclusion, our workflow allows a functional separation of differentially glycosylated IgG Fc. Consequently, applicability of FcɣRIIIa AC-MS is extended to Fab glycosylated IgG, i.e. cetuximab, by significantly reducing ambiguities in glycoform assignment versus intact analysis.